2021
DOI: 10.1097/mat.0000000000001388
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Viscoelastic Testing in Pediatric Patients Using the Pediatric Extracorporeal Membrane Oxygenation Outcomes Registry

Abstract: Use of viscoelastic tests (VETs), including thromboelastography (TEG) and rotational thromboelastometry (ROTEM), is increasing in the management of anticoagulation in extracorporeal membrane oxygenation (ECMO) patients. A retrospective review of data on 265 pediatric (<20 years old) ECMO patients who underwent VET and were submitted to the Pediatric ECMO Outcomes Registry (PEDECOR) was conducted to describe common coagulopathies in patients who underwent VET; associations between the VET parameters and traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We conducted a retrospective observational cohort study using multicenter Pediatric ECMO Outcomes Registry (PEDECOR) data from October 2011 to June 2019. PEDECOR was built using a secure web-based data platform housed at the Baylor College of Medicine Dan L. Duncan Institute for Clinical and Translational Research (16, 17). The registry includes all patients who undergo ECMO at each participating center and collects data including demographics, preadmission diagnoses, pre-ECMO course, ECMO mode and course characteristics, laboratory results and medications, and transfusions administered during the ECMO course, as well as post-ECMO disposition.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a retrospective observational cohort study using multicenter Pediatric ECMO Outcomes Registry (PEDECOR) data from October 2011 to June 2019. PEDECOR was built using a secure web-based data platform housed at the Baylor College of Medicine Dan L. Duncan Institute for Clinical and Translational Research (16, 17). The registry includes all patients who undergo ECMO at each participating center and collects data including demographics, preadmission diagnoses, pre-ECMO course, ECMO mode and course characteristics, laboratory results and medications, and transfusions administered during the ECMO course, as well as post-ECMO disposition.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies investigated the role of TEG among pediatric patients undergoing general surgical procedures and they found that applying TEG or ROTEM in pediatric patients increased coagulopathy risk and blood products use [ 188 ] while in neonates, TEG parameters predicted sepsis early [ 189 ]. Also, TEG-guided transfusion decreased blood products use compared to clinician-guided transfusion while in mortality and morbidity risks, no differences were detected [ 190 ].…”
Section: Reviewmentioning
confidence: 99%
“…Figures 3, 4 describe the clinical features and TEG R /ROTEM R parameters that have been associated with increased bleeding and thrombotic complications. In a recent report using data from 265 children in the Pediatric ECMO Outcomes Registry (PEDECOR) VET was utilized in ¾ of centers contributing data, although bleeding and thrombotic complications were not different between centers utilizing VET compared to centers that did not (60). We review these pediatric studies below and in Table 3.…”
Section: Evidence To Support Vet Use In Ecmo and Vadmentioning
confidence: 99%
“…Alexander et al found a weak correlation of the TEG R heparinase variables and the aPTT/ACT, but a stronger correlation between the TEG R MA and platelet count (62). In the PEDECOR study, VET identified platelet dysfunction most commonly and bleeding patients who had VET performed received more cryoprecipitate transfusions than those who did not have VET (60). A chart review of children <18 years on ECMO looked at severe platelet dysfunction (<50% aggregation on TEG R PM) and bleeding.…”
Section: Vet Impact On Bleedingmentioning
confidence: 99%